Altered Interoceptive Awareness in High Habitual Symptom Reporters and Patients With Somatoform Disorders - Flasinski, Tabea; Dierolf, Angelika Margarete; Rost, Silke; Lutz, Annika P. C.; Voderholzer, Ulrich; Koch, Stefan; Bach, Michael; Asenstorfer, Carina; Münch, Eva Elisabeth; Mertens, Vera-Christina; Vögele, Claus; Schulz, André (Frontiers in Psychology, 2020)
Objective. Altered interoception may play a major role in the etiology of medically unexplained symptoms (MUS). It remains unclear, however, if these alterations concerns noticing of signals or if they are limited to the interpretation of signals. We investigated whether individuals with MUS differ in interoceptive awareness as assessed with the Multidimensional Assessment of Interoceptive Awareness (MAIA) questionnaire. Methods. Study 1: 486 individuals completed the Screening for Somatoform Disorders (SOMS-2). 32 individuals each of the upper and lower decile of the SOMS distribution (low symptom reporters/LSR, high symptom reporters/HSR) completed the MAIA. Study 2: MAIA scores of individuals diagnosed with somatoform disorder (SFD; n = 26) were compared to individuals with major depressive disorder (MDD; n = 25) and healthy controls (HC; n = 26). Results. HSR had lower scores than LSR on the MAIA scales Not-Distracting and Not-Worrying. The SFD and MDD groups showed lower scores than HC on the MAIA scales Not-Distracting, Self-Regulation, and Trusting. The MDD group scored lower than the other two groups on the scales Body Listening and Attention Regulation. There were no group differences on the scale Noticing. Conclusion. HSR, SFD and MDD patients do not differ from HC in the awareness of noticing of interoceptive signal processing, whereas cognitive facets of interoception, such as distraction or self-regulation are differentially affected. This highlights the necessity of including specifically targeted interventions, which improve interoceptive awareness, in the prevention and treatment of SFDs.